2020
DOI: 10.3892/mmr.2020.11634
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite motif‑containing 14 regulates cell proliferation and apoptosis in cervical cancer via the Akt signaling pathway

Abstract: Tripartite motif-containing (TriM) 14 is a protein of the TriM family. Studies have indicated that TriM14 may be used as an oncogene in tumor cells, such as osteosarcoma, non-small cell lung cancer and breast cancer through different pathways. However, the functions of TriM14 in cervical cancer cells remain unclear. Therefore, this study aimed to investigate the functions of TriM14 in cervical cancer cells and its underlying mechanism. caski cells stably expressing TriM14 and SiHa, and Hela cells stably expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…TRIM protein families pertain to the pathogenesis of multiple human cancers, taking part in the modulation of many cellular functions. For instance, TRIM14 expression is elevated in diverse cancers, such as gastric cancer and cervical cancer [ 18 , 19 ]. Overexpressed TRIM14 can bolster breast cancer cell proliferation, adding to the malignancy of colorectal cancer [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM protein families pertain to the pathogenesis of multiple human cancers, taking part in the modulation of many cellular functions. For instance, TRIM14 expression is elevated in diverse cancers, such as gastric cancer and cervical cancer [ 18 , 19 ]. Overexpressed TRIM14 can bolster breast cancer cell proliferation, adding to the malignancy of colorectal cancer [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it also controls the levels of the MDM2 protooncogene (MDM2) and AKT serine/threonine kinase 1 (AKT1), thereby increasing the levels of TP53, BAX, and cyclin-dependent kinase inhibitor 1A (CDKN1A), leading to increased apoptosis under ionizing radiation [ 167 , 168 ]. Diao et al reported that TRIM14 is highly expressed in human cervical cancer cells and regulates cell proliferation and death through the AKT1 pathway [ 169 ]. In contrast, TRIM14 is inhibited to protect against cerebral ischemia injury, which is regulated by NFKB/NLRP pathway-mediated apoptosis [ 170 ].…”
Section: Guardians Of Cell Fate: Trim Proteins and Their Regulation O...mentioning
confidence: 99%
“…This inhibition is accomplished through the regulation of transcription factors and mediation of signaling molecules crucial for the EMT process, which is essential for cell migration and invasion. Notably, TRIM3 downregulates the expression of EMT transcription factors, such as Snail, Slug, and TWIST, thus curbing the EMT process in cervical cancer cells and weakening their migration and invasion potentials (Diao et al 2020 ). Furthermore, TRIM3 overexpression exhibits tumor-inhibiting effects in cervical cancer.…”
Section: The Role Of Trim3 In Antitumorigenesis and Tumor Developmentmentioning
confidence: 99%
“…Furthermore, TRIM3 overexpression exhibits tumor-inhibiting effects in cervical cancer. Research reveals that TRIM3 reduces the population of cervical cancer tumor stem cells and actively participates in regulating their apoptosis and differentiation by engaging various signaling pathways (Diao et al 2020 ). Moreover, TRIM3 overexpression effectively suppresses angiogenesis, resulting in decreased tumor blood supply and growth.…”
Section: The Role Of Trim3 In Antitumorigenesis and Tumor Developmentmentioning
confidence: 99%